Digital government at work : a social informatics perspective - McLoughlin, Ian, 1956-; Wilson, Rob; Martin, M. (Mike), 1949- (Oxford : Oxford University Press, 2013)
Drawing upon extensive research from inside live projects, this book examines the use of digital technologies to provide more joined-up public services, and combines cross-disciplinary insights to provide a new social informatics perspective on digital government.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 24, 2013).
Keywords: Internet in public administration; Electronic government information